(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Stroke is the second commonest cause of death in developed countries. It is responsible for severe physical disability of a large population. The study was designed to see the association of serum procalcitonin concentration (PCT) with outcome of acute ischemic stroke (AIS) patients. Methods: This study was a prognostic cohort study. A total number of 60 patients, aged 18 years and above, presenting with AIS, from 0 day to 3 days were enrolled in this study. Blood sample was collected for estimation of serum PCT concentration. Modified Rankin Scale (mRS) was done after 1 month of stroke. Unfavorable outcome was defined as mRS>2 and favorable outcome as 0-2. Results: Patients with unfavorable outcome had significant higher serum PCT concentration than patients with favorable outcome (271.82 ± 130.33 vs.128.51 ± 113.91). A positive correlation (r =0.418) was found between mRS score and serum procalcitonin concentration, which was also significant (p<0.001).On logistic regression analysis, higher serum PCT concentration remained independent predictor of unfavorable outcome ofAIS patients (p=0.009, Odds Ratio = 1.027). Conclusion: Higher serum PCT concentration is associated with unfavorable outcome ofAIS.